Revival : a novel - King, Stephen, 1947- (New York : Simon & Schuster, Inc., 2014)
In a small New England town over half a century ago, a boy is playing with his new toy soldiers in the dirt in front of his house when a shadow falls over him. He looks up to see a striking man, the new minister, Jamie learns later, who with his beautiful wife, will transform the church and the town. The men and boys are a bit in love with Mrs. Jacobs; the women and girls, with the Reverend Jacobs-- including Jamie's sisters and mother. Then tragedy strikes, and this charismatic preacher curses God, and is banished from the shocked town.
Keywords: Drug addicts -- Fiction; Clergy -- Fiction; Rock musicians -- Fiction; Religious fanaticism -- Fiction; Life change events -- Fiction; Good and evil -- Fiction; Death -- Fiction; Suspense fiction